Ethics and employees role for effective corporate governance in Malaysian private sectors - Kanageswary, Batumalai (2022)
Effective corporate governance is essential for companies to operate their business activities in more efficiently, increase access to capital, prevent threat, and give priority for best interest of stakeholders. Effective governing practices will encourage employees to behave ethically in daily business operation. Presently, governance in the private sectors exposed to criticism because of the governance failure such as poor internal control, employees involvement in fraudulent activities, corruption and bribery. Thus, the purpose of this study is to determine how important ethics among employees and their role as transparency, accountability, responsibility, loyalty, consensus oriented and participation for effective corporate governance in Malaysian private sectors. For this study, the researcher has used a quantitative method and the data was collected using survey method by constructing a self-administered questionnaire. The questionnaires were distributed among the private sectors employees especially majority of the respondents working in Klang Valley and only 150 of the data were used for this analysis. The data analysis that was used for this study are descriptive analysis, reliability test, Cronbach Alpha, and regression analysis. The result of this study indicates that there is a significant exists between employees role as participation for effective corporate governance in private sectors. However, the result indicates that there is insignificant exists between employees role as transparency, accountability, responsibility, loyalty and consensus oriented for effective corporate governance in privates sectors. Furthermore, it is also found that employees behave ethically for effective corporate governance are moderate to strong level. Therefore, the government of Malaysia need to initiate proper strategies to enhance the effectiveness of corporate governance in private sectors which help to increase the growth of economy into the next level.